Belo Horizonte "democrática-popular": uma análise descritiva das instituições de participação popular em Belo Horizonte - Ana Flavia Martins Machado (2007)
Since 1988s Constitution, and as a consequence of it, the country has been experiencing new models of institutions of popular participation, as a way to incentive the participation of civil society in public politics discussion and definition, spaces until then occupied exclusively by governments. In Belo Horizonte, it can be observed, since 1993, when Party of Workers assumed municipal government, an increasing number of these institutions, especially of public politics councils and commissions, actuating in several areas of local government. This dissertation presents a view describing these institutions, starting from a survey and analysis of formal definitions and its functioning rules, and describes its main characteristics. From this survey, this dissertation intends to indicate possible limits and/or potentials of these institutions in democratization municipal administration in analysis